Так говорил Заратустра: Пер. с нем. / Ф. Ницше - Ницше Фридрих (Философия. Мастера, 1999)
Экземпляры: (20171128) / Инвентарный номер: 1991 / Цена: / Сис.шифр: 87.3(4Гем) / Авт.знак: Н 70 / ББК: 87.3(4Гем)